2021
DOI: 10.1002/jpen.2107
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in medical education in Latin America: Results of a cross‐sectional survey

Abstract: Rationale The gap between the nutrition education provided to medical students and the nutrition competences and attitudes needed for doctors to provide effective nutrition care is a global concern. The goal of this study was to investigate the curricular content on nutrition education in Latin American medical schools and to evaluate the self‐perceived knowledge, attitudes, and barriers to nutrition practice of final‐year medical students. Methods Eighty‐five public and private medical schools from 17 Latin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 39 publications
0
6
0
17
Order By: Relevance
“…This study showed that for a total of 22 out of 85 surveyed medical school deans, the mean hours dedicated to nutrition education was 47 (range, 0–150). Most students (n = 1483, 91%) agreed that improving patients’ health through nutrition is important and that nutrition counseling and assessment should be part of all physicians’ routine care, but they lack the level of education and training required to address nutrition‐related issues 10 . These data align with evidence of persistent gaps in medical nutrition education and training in the US and Europe 11–13 .…”
Section: Introductionmentioning
confidence: 75%
“…This study showed that for a total of 22 out of 85 surveyed medical school deans, the mean hours dedicated to nutrition education was 47 (range, 0–150). Most students (n = 1483, 91%) agreed that improving patients’ health through nutrition is important and that nutrition counseling and assessment should be part of all physicians’ routine care, but they lack the level of education and training required to address nutrition‐related issues 10 . These data align with evidence of persistent gaps in medical nutrition education and training in the US and Europe 11–13 .…”
Section: Introductionmentioning
confidence: 75%
“…Esta vulnerabilidad se ve agravada por el hecho de que la malnutrición o las enfermedades y afecciones relacionadas con la malnutrición carecen de reconocimiento y sensibilización por parte de los profesionales de la salud de forma más general. Esto puede explicarse, en parte, por la falta de educación nutricional, tanto a nivel de grado como de posgrado (28,29) . Así, la desnutrición implica una «doble vulnerabilidad» para el paciente: la primera, la del detrimento físico o mental; mientras que la segunda se da por el alto desconocimiento y la falta de educación sobre la nutrición clínica entre los profesionales sanitarios (19) .…”
Section: Marco éTico En El áMbito De Los Cuidados Nutricionales El Principio De Respeto a La Vulnerabilidad Humana Y A La Integridad Persunclassified
“…De acuerdo con la evidencia, la problemática que representa la DAE está agravada por la práctica con desconocimiento o la ausencia de la misma, que desde la ética biomédica puede ser entendida como negligencia. Esto es así porque se ha demostrado que no hay una preparación adecuada del personal médico ni de enfermería en cuanto a la educación en nutrición clínica, siendo reconocida esa deficiencia por ellos mismos (10,11) .…”
Section: Discusión No Maleficencia: Primero No Dañarunclassified
“…La evidencia muestra que, a pesar de la formación deficiente en materia de nutrición clínica de todo el personal de salud, existe el interés para saber más acerca de esta (10,19) mediante la colaboración para la práctica en el ámbito clínico nutricional (20) , ya que la calidad de la terapia nutricional también es cuestión de la identificación y monitorización de los actores involucrados en el equipo multidisciplinario, especialmente personal médico y de enfermería (11) .…”
Section: Educar: Posible Soluciónunclassified